ANALISIS KESESUAIAN PENGUNGKAPAN DANA KEBAJIKAN DAN DANA NON HALAL DALAM CATATAN ATAS LAPORAN KEUANGAN BANK SYARIAH DI ERA DIGITAL - Nur Aisyah; Indrih Br Harahap; Hasta La Victoria Siempre; M Royhan Safdan Muzaki Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2026)
The development of digital technology has driven a transformation in the Islamic banking financial reporting system, demanding increased transparency and accountability of information. One important aspect of Islamic bank financial reports is the disclosure of charitable and non-halal funds, reflecting compliance with sharia principles and the institution's social responsibility. Charity funds are funds originating from social sources and used for the benefit of the community, while non-halal funds are funds obtained from transactions that do not comply with sharia principles and must be managed and distributed in accordance with applicable regulations. This study aims to analyze the appropriateness of disclosure of charitable and non-halal funds in the Notes to the Financial Statements (CaLK) of Islamic banks in Indonesia in the digital era. The study used a qualitative descriptive method with a content analysis approach to the financial statements and annual reports of Islamic banks. The analysis was conducted by comparing the disclosure practices of Islamic banks with the provisions contained in PSAK 101 and the Indonesian Islamic Banking Accounting Guidelines (PAPSI). The results are expected to provide an overview of the level of compliance of Islamic banks in disclosing charitable and non-halal funds and demonstrate the role of digitalization in increasing transparency and accountability in Islamic financial reporting.